Hunde in der römischen Antike : Rassen/Typen - Zucht - Haltung und Verwendung - Autengruber-Thüry, Heidelinde, (Archaeopress Roman archaeology ;, 2021)
This title deals extensively with the living environment of the dog in Roman antiquity, based on literary and iconographic sources as well as archaeological and archaeozoological finds. The knowledge gained from this is documented by numerous images. Older research opinions, some of which have gone unchecked for more than a hundred years, are examined and - where necessary - corrected. For the first time, a catalogue of the more than 80 dog breeds/types documented from antiquity is presented with their names, origins, appearance and the special characteristics of these animals. The ancient theories of dog breeding are compared with modern practices.